Frequency and degradation of SARS-CoV-2 markers N1, N2, and E in sewage. (10th April 2023) - Hart, John J.; Jamison, Megan N.; McNair, James N.; Szlag, David C.
Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease that is mainly spread through aerosolized droplets containing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is excreted in feces by infected individuals. Sewage surveillance has been applied widely to obtain data on the prevalence of COVID-19 in whole communities. We used SARS-CoV-2 gene targets N1, N2, and E to determine the prevalence of COVID-19 at both municipal and building levels. Frequency analysis of wastewater testing indicated that single markers detected only 85% or less of samples that were detected as positive for SARS-CoV-2 with the three markers combined, indicating the necessity of pairing markers to lower the false-negative rate. The best pair of markers in both municipal and building level monitoring was N1 and N2, which correctly identified 98% of positive samples detected with the three markers combined. The degradation rates of all three targets were assessed at two different temperatures (25 and 35 °C) as a possible explanation for observed differences between markers in frequency. Results indicated that all three RNA targets degrade at nearly the same rate, indicating that differences in degradation rate are not responsible for the observed differences in marker frequency. HIGHLIGHTS: There is a knowledge gap regarding the expression frequency and degradation of SARS-CoV-2 in wastewater. This study looks at the frequency and degradation of three RNA molecular markers commonly used in wastewater-based epidemiology (WBE). Results indicate the best combination of RNA markers and their average decay kinetics. This study will aid in future WBE monitoring and modeling efforts for SARS-CoV-2. Graphical Abstract